KIMBERLITES OF EASTERN PRIAZOV'E (UKRAINE) AND GEOCHEMICAL CHARACTERISTICS OF THEIR SOURCES - Yutkina E.V.; Kononova V.A.; Bogatikov O.A.; Knyaz'kov A.P.; Kozar N.A.; Ovchinnikova G.V.; Levsky L.K. (My University, 2004)
A combined petrological, geochemical, and mineralogical study of Kimberlites of eastern Priazov'e was described. A reliable criteria for the identification of these rocks, to characterize their sources, and to assess their possible diamond potential was obtained. Kimberlites and basalts were made up of common geologic units and were derived from mantle reservoirs subjected to different degrees of depletion. The kimberlites of eastern Priazov'e are similar in composition to the kimberlites from the Kepinskoe field of the Arkhangelsk province and other areas of the northern part of the East European platform.
Keywords: Kimberlites; eastern Priazov'e